APPLICATION OF LASERS IN CLINICAL DENTISTRY - Pardeep, Singh; Kirtika, Sheoran; Gyanander, Attresh; Sandeep, Manchanda (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
Laser light is monochromatic, directional and coherent. Laser is one of the most captivating technologies in dental practice. Albert Einstein theorized a phenomenon termed as “Stimulated emission’’, the principle on which all lasers work. All lasers are named based on the active medium that is responsible for stimulating them.. The active medium can be a gas, a liquid or a solid state crystal rod or a semiconductor (diode lasers). These highly directional and monochromatic laser lights can be delivered on to target tissue as a continuous wave, gated-pulse mode or free running pulse mode. Various laser delivery systems are -Articulated arms, Hollow waveguides, Fiber optics. Among which later one is system of choice for most of lasers. This article gives an insight on laser science and instrument used in dentistry. Lasers are impressive potential treatment modality for variety of clinical conditions. This article profile several clinical application in clinical dentistry